A hierarchical porous skin-core structure aerogel fiber and a preparation method and application thereof

CN122898984APending Publication Date: 2026-10-13DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611398727.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种层级多孔皮芯结构气凝胶纤维及其制备方法和应用,解决现有气凝胶纤维多孔网络与力学性能难以同时兼顾的技术难题

Benefits of technology

(1)本发明采用PAN为皮层、共轭COF分散液为芯层,搭配酸性凝固浴质子诱导自组装工艺制备同轴气凝胶纤维,致密PAN皮层可对内层多孔骨架形成物理保护,芯层连续贯通层级多孔结构赋予纤维优异隔热能力,有效解决传统气凝胶纤维多孔结构与力学性能无法兼顾的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898984A_ABST
    Figure CN122898984A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of fiber preparation, and specifically discloses a hierarchical porous skin-core structure aerogel fiber and a preparation method and application thereof. The method uses polyacrylonitrile solution as a skin layer spinning stock solution, two-dimensional covalent organic framework dispersion liquid as a core layer spinning liquid, and an acid aqueous solution as a coagulation bath, realizes synchronous coagulation of the skin-core tows by relying on solvent bidirectional diffusion, and is stably formed by matching a multistage washing, low-temperature freezing, and vacuum freeze-drying whole set of post-processing process. The skin-core aerogel fiber is prepared by using a coaxial wet spinning and freeze-drying combined process. The fiber prepared by the application has a continuous and dense polymer skin layer on the outer layer, and a continuous and interconnected hierarchical porous core layer skeleton is formed in the inside. The formed fiber is complete and continuous, effectively solves the processing problems such as core layer agglomeration, internal pore collapse, and skin-core layering that are prone to occur in conventional wet spinning, and endows the skin-core aerogel fiber with excellent mechanical properties and heat insulation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fiber preparation technology, specifically relating to a layered porous core-sheath structure aerogel fiber, its preparation method, and its application. Background Technology

[0002] Aerogels, due to their unique porous structure, possess ultra-low density, ultra-high porosity, large specific surface area, and extremely low thermal conductivity, making them promising candidates for applications in thermal insulation, environmental treatment, energy storage and conversion, catalysis, and electromagnetic absorption and shielding. However, traditional aerogels are mostly bulk or film-shaped two-dimensional or three-dimensional molding materials with low mechanical strength and poor flexibility, making them difficult to directly process and mold, which greatly limits their application in the field of flexible materials.

[0003] If aerogels are processed into continuous fiber forms, while retaining the advantages of ultra-high porosity and low density, the fibers can be given flexibility and processability, which can greatly broaden the application scenarios of aerogels. However, aerogel fibers generally have an inherent contradiction: high porosity can significantly improve thermal insulation, but it will cause a significant decrease in the tensile strength and toughness of the material. It is difficult to balance porous structure and mechanical properties, which is a key problem that urgently needs to be solved in this field.

[0004] The prior art discloses a biomimetic gradient porous aerogel fiber and its preparation method. The core-shell fiber with a dense outer layer and a loose core layer is obtained by wet cryogenic spinning. Although it initially achieves a balance between porosity and mechanical properties, the overall mechanical strength of the fiber is low, the continuity of the porous structure of the core layer is poor, and there is still a lot of room for improvement in the comprehensive performance. Summary of the Invention

[0005] The purpose of this invention is to provide a layered porous core-shell structure aerogel fiber, its preparation method, and its application, thereby solving the technical problem that existing aerogel fibers cannot simultaneously achieve both porous network and mechanical properties.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing layered porous core-shell structured aerogel fibers, comprising the following steps: Step 1: Dissolve polyacrylonitrile in an organic solvent to obtain polyacrylonitrile stock solution; Step 2: Disperse DABA-TFP-COF in an organic solvent to obtain a COF dispersion; Step 3: Using polyacrylonitrile stock solution as the sheath spinning solution and COF dispersion as the core spinning solution, coaxial wet spinning is carried out, and the fibers are extruded into an acidic aqueous solution coagulation bath to form nascent sheath-core hydrogel fibers. Step 4: The nascent core-skin hydrogel fibers are sequentially freeze-molded and vacuum freeze-dried to obtain the hierarchical porous core-skin structure aerogel fibers; There is no restriction on the order of steps 1 and 2.

[0007] Preferably, in step 1, the organic solvent includes at least one of dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; The concentration of polyacrylonitrile in the polyacrylonitrile stock solution is 150~250 mg / mL.

[0008] Preferably, in step 2, the organic solvent includes at least one of dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; The concentration of DABA-TFP-COF in the COF dispersion is 10~20 mg / mL; The dispersion includes: ultrasonic dispersion followed by a constant-temperature reaction; the ultrasonic dispersion time is 1-2 hours; the constant-temperature reaction temperature is 40-60°C, and the time is 6-8 days; After the isothermal reaction, the process further includes sequential cooling and static degassing; the cooling is natural cooling to room temperature; the static degassing time is 4~12h.

[0009] Preferably, during the coaxial wet spinning process, the propulsion speed of the sheath spinning solution is 100~200μL / min, the propulsion speed of the core spinning solution is 80~180μL / min, and the propulsion speed of the sheath spinning solution is greater than that of the core spinning solution.

[0010] Preferably, the acidic aqueous solution includes at least one selected from hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution, methanesulfonic acid aqueous solution, and p-toluenesulfonic acid aqueous solution; the pH value of the acidic aqueous solution coagulation bath is 2.5~2.8; The impregnation molding time is 20-30 minutes.

[0011] Preferably, before the freeze-forming process, the nascent core-sheath hydrogel fiber is further subjected to multiple soaking and washing processes; the soaking and washing processes are carried out at room temperature using deionized water; the time for each soaking and washing process is 10-30 minutes, and the number of soaking and washing processes is 3-5 times.

[0012] Preferably, the freezing temperature is -18 to -25°C and the freezing time is 6 to 12 hours; The vacuum freeze-drying temperature is -40~-50℃, the time is 24~48h, and the vacuum degree of the drying chamber is ≤10Pa.

[0013] The present invention also provides a layered porous core-sheath structure aerogel fiber prepared by the preparation method described above, wherein the fiber sheath of the layered porous core-sheath structure aerogel fiber is a dense porous PAN sheath, and the core layer is a continuous through-layered porous skeleton formed by DABA-TFP-COF self-assembly.

[0014] Preferably, the pore size of the fiber sheath is 100~200nm; the pore size of the core layer is 100~300μm.

[0015] This invention also provides the application of the layered porous core-shell structure aerogel fiber described in the above technical solution in the field of low-temperature thermal insulation and lightweight thermal insulation functional materials.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention uses PAN as the skin layer and conjugated COF dispersion as the core layer, and uses an acidic coagulation bath proton-induced self-assembly process to prepare coaxial aerogel fibers. The dense PAN skin layer can form physical protection for the inner porous skeleton, and the continuous through-layer porous structure of the core layer gives the fiber excellent thermal insulation ability, effectively solving the defect that the porous structure and mechanical properties of traditional aerogel fibers cannot be taken into account at the same time.

[0017] (2) This invention relies on hydrogen ion regulation in coagulation bath to stack COF nanosheets, eliminating the need for additional pore-forming agents such as carbonates and foaming agents, simplifying the spinning solution formulation system. The core layer pore size distribution and pore continuity can be precisely controlled by adjusting the pH of the coagulation bath and the soaking time, resulting in strong process controllability.

[0018] (3) The entire preparation process adopts room temperature liquid preparation and low temperature freeze drying process, without high temperature treatment throughout the process, to avoid the shrinkage and collapse of the internal porous skeleton caused by high temperature, and to preserve the original hierarchical pore structure of the aerogel to the greatest extent.

[0019] (4) The present invention adopts dual-channel coaxial synchronous extrusion molding, with independent adjustable internal and external pump speeds. The high-flow-rate solution in the skin layer completely encapsulates the core layer, enabling continuous filament spinning. The preparation process is simple and easy to scale up for production. Attached Figure Description

[0020] Figure 1 The images shown are scanning electron microscope (SEM) images of the aerogel fibers prepared in Example 1, where (a) is a cross-sectional view of the complete fiber, (b) is a magnified view of the core-sheath junction, (c) is a magnified view of a portion of the core layer, and (d) is a magnified view of a portion of the sheath layer. Figure 2 Scanning electron microscope images of aerogel fibers from Examples 1-3 and Comparative Example 1; Figure 3 The tensile stress-strain curves of aerogel fibers obtained in Examples 1-3 and Comparative Example 1 are shown. Figure 4 The graph shows a comparison of the steady-state temperature difference between the aerogel fibers obtained in Examples 1-3 and Comparative Example 1 and the hot stage. Detailed Implementation

[0021] This invention provides a method for preparing layered porous core-shell structured aerogel fibers, comprising the following steps: Step 1: Dissolve polyacrylonitrile in an organic solvent to obtain polyacrylonitrile stock solution; Step 2: Disperse DABA-TFP-COF in an organic solvent to obtain a COF dispersion; Step 3: Using polyacrylonitrile stock solution as the sheath spinning solution and COF dispersion as the core spinning solution, coaxial wet spinning is carried out, and the fibers are extruded into an acidic aqueous solution coagulation bath to form nascent sheath-core hydrogel fibers. Step 4: The nascent core-skin hydrogel fibers are sequentially freeze-molded and vacuum freeze-dried to obtain the hierarchical porous core-skin structure aerogel fibers; There is no restriction on the order of steps 1 and 2.

[0022] Step 1 of the present invention involves dissolving polyacrylonitrile in an organic solvent to obtain a polyacrylonitrile stock solution.

[0023] In this invention, the organic solvent preferably includes at least one selected from dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; the concentration of polyacrylonitrile in the polyacrylonitrile stock solution is preferably 150-250 mg / mL (specifically, it can be 150 mg / mL, 200 mg / mL, or 250 mg / mL). In this invention, the dissolution is preferably carried out under stirring conditions, the stirring temperature is preferably room temperature, and the stirring time is preferably 10-16 h (specifically, it can be 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, or 16 h). In this invention, the above-mentioned organic solvent has excellent dissolving ability for polyacrylonitrile, which can quickly achieve uniform dispersion and dissolution of polyacrylonitrile, resulting in a spinning stock solution with excellent flow properties, facilitating subsequent coaxial spinning.

[0024] Step 2 of this invention involves dispersing DABA-TFP-COF in an organic solvent to obtain a COF dispersion.

[0025] In this invention, the DABA-TFP-COF is a two-dimensional covalent organic framework material obtained by Schiff base condensation of 2,5-diaminobenzenesulfonic acid (DABA) and 1,3,5-tricarboxymethylresorcinol (TFP) followed by enol-ketone tautomerism, belonging to the typical β-ketoenamine COF. The preferred preparation method of the DABA-TFP-COF in this invention includes: weighing 0.286 mg of 2,5-diaminobenzenesulfonic acid (DABA, 99%) and 0.214 mg of 1,3,5-tricarboxymethylresorcinol (TFP, 97%); dissolving DABA in 10 mL of dimethyl sulfoxide (DMSO) and TFP in 15 mL of DMSO; ultrasonicating both solutions until completely dissolved into a clear solution; then pouring the DABA solution into the TFP solution; shaking thoroughly; and reacting in a 60°C oven for 5 days to obtain DABA-TFP-COF.

[0026] In this invention, the organic solvent preferably includes at least one selected from dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; the concentration of DABA-TFP-COF in the COF dispersion is 10-20 mg / mL (specifically, it can be 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, or 20 mg / mL); the dispersion preferably includes: ultrasonic dispersion followed by a isothermal reaction; the ultrasonic dispersion time is preferably 1-2 hours; the isothermal reaction temperature is preferably 40-60°C. The temperature can be 40℃, 50℃, or 60℃, and the preferred time is 6-8 days, specifically 6, 7, or 8 days. The isothermal reaction is preferably carried out under sealed and light-proof conditions. The isothermal reaction allows the two monomers to alternately link together to form a cyclic macromolecule. After the isothermal reaction, it is also preferred to perform cooling and static degassing sequentially. The cooling is preferably natural cooling to room temperature. The static degassing time is preferably 4-12 hours (specifically 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, or 12h). Static degassing eliminates microbubbles inside the dispersion, avoiding defects such as pores, cracks, and broken fibers during spinning, ensuring a uniform and complete overall fiber bundle structure. In this invention, no additional foaming agent is added during the preparation of the COF dispersion; the self-assembly of the layers and the creation of pores are achieved through proton induction in the coagulation bath.

[0027] In this invention, if the concentration of the COF dispersion is too low, the number of COF nanosheets in the system will be insufficient, and a continuous, interconnected porous network cannot be formed after molding; if the concentration is too high, the viscosity of the dispersion will increase significantly, the fluid flow will deteriorate, and problems such as fiber breakage and uneven fiber output will easily occur during the spinning process. This invention limits the concentration of the COF dispersion to the range of 10~20 mg / mL. Within this concentration range, the dispersion has moderate fluidity, the spinning is continuous and stable, and a complete hierarchical porous framework can be formed in the core layer after molding.

[0028] After obtaining the polyacrylonitrile stock solution and the COF dispersion, step 3 of the present invention involves using the polyacrylonitrile stock solution as the sheath spinning solution and the COF dispersion as the core spinning solution to perform coaxial wet spinning, extruding the fibers into an acidic aqueous solution coagulation bath for wetting and molding, thereby obtaining nascent sheath-core hydrogel fibers.

[0029] In this invention, during the coaxial wet spinning process, the preferred propulsion speed of the sheath spinning solution is 100-200 μL / min (specifically, it can be 100 μL / min, 120 μL / min, 140 μL / min, 150 μL / min, 160 μL / min, 180 μL / min, or 200 μL / min), and the preferred propulsion speed of the core spinning solution is 80-180 μL / min (specifically, it can be 80 μL / min, 100 μL / min, 120 μL / min, or 200 μL / min). The flow rates are 140 μL / min, 160 μL / min, and 180 μL / min, and the extrusion flow rate of the sheath spinning solution is preferably greater than that of the core spinning solution to achieve complete sheath coating of the core layer and avoid core liquid leakage and spinning breakage defects. The sheath PAN solution has a higher viscosity, and the use of high flow rate can quickly form a complete coating layer to avoid core liquid leakage and sheath-core delamination failure. The core COF dispersion has a lower viscosity, and low-speed extrusion ensures that the COF sheets have sufficient time to complete self-assembly in an acidic environment. The PAN spinning solution is connected to the outer channel of the coaxial needle, and the COF dispersion is connected to the inner channel of the coaxial needle. The dual pumps push the solution independently at a uniform speed to complete coaxial wet spinning. By matching the bidirectional diffusion rate of the solvent through the speed difference between the inner and outer pumps, the sheath solidification and the porous skeleton of the core layer are constructed simultaneously to obtain coaxial fibers with stable morphology and structure, while simultaneously taking into account mechanical properties and internal porous thermal insulation structure.

[0030] In this invention, the acidic aqueous solution preferably includes at least one of hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution, methanesulfonic acid aqueous solution, and p-toluenesulfonic acid aqueous solution; the pH value of the acidic aqueous solution coagulation bath is preferably 2.5~2.8, more preferably 2.8; the immersion and molding time is preferably 20~30 min (specifically 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, 30 min); the selected acidic aqueous solution does not undergo corrosive or decomposition chemical reactions with the PAN skin layer and DABA-TFP-COF core layer. In this invention, the acidity of the coagulation bath directly controls the stacking behavior of COF nanosheets. If the acidity is too high, proton diffusion is too fast, the sheets quickly aggregate and compact, and the honeycomb channels collapse over a large area; if the acidity is too low, the proton content is insufficient, the sheet repulsion is too large, only scattered pores are formed, and a continuous porous network cannot be formed. A complete hierarchical porous core layer can be achieved with a pH value in the range of 2.5~2.8.

[0031] In this invention, during the impregnation molding process, the polyacrylonitrile (PAN) stock solution undergoes bidirectional solvent diffusion and phase separation in an acidic aqueous solution coagulation bath. When the PAN spinning solution is extruded into the acidic aqueous solution system, the solvent inside the fiber diffuses rapidly outward, while hydrogen ions and water molecules in the coagulation bath penetrate inward, causing the PAN concentration on the fiber surface to quickly reach supersaturation and liquid-liquid phase separation to occur. As the solvent continues to precipitate outward, the hydrogen bond forces between PAN molecular chains are continuously rebuilt, forming a dense and continuous skin layer.

[0032] This invention eliminates the need for external pore-forming fillers such as carbonates and foaming agents. It relies on hydrogen ions in the coagulation bath to neutralize the negative charge on the surface of COF sheets, thereby regulating the electrostatic repulsion of the sheets to achieve self-assembly and pore formation. After hydrogen ions diffuse inward in the coagulation bath, the sulfonic acid groups on the COF surface are protonated, reducing the repulsion between the sheets. Interconnected honeycomb channels are formed spontaneously by intermolecular hydrogen bonds and van der Waals forces, simplifying the spinning solution formulation and avoiding the impact of residual external fillers on the long-term stability of the fiber.

[0033] After obtaining the nascent core-skin hydrogel fiber, step 4 of the present invention involves sequentially freezing and freezing the nascent core-skin hydrogel fiber to obtain the layered porous core-skin structure aerogel fiber.

[0034] Before the cryogenic molding, the present invention preferably includes repeatedly soaking and washing the nascent core-sheath hydrogel fibers. The soaking and washing is preferably carried out at room temperature using deionized water. The soaking and washing time for each time is preferably 10-30 minutes (specifically 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes), and the number of times is preferably 3-5 times (specifically 3 times, 4 times, or 5 times) until the washing water is clear and no impurities are precipitated. The soaking and washing removes free acidic substances and residual solvents.

[0035] In this invention, the preferred freezing temperature is -18 to -25°C (specifically -18°C, -20°C, -22°C, -25°C), and the preferred time is 6 to 12 hours (specifically 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours). The preferred freezing method is flat-laying without compression and low-temperature freezing. In this invention, the preferred vacuum freeze-drying temperature is -40 to -50°C (-40°C, -45°C, -50°C), and the preferred time is 24 to 48 hours (specifically 24 hours, 30 hours, 36 hours, 42 hours, 48 ​​hours). The vacuum degree of the drying chamber is ≤10 Pa (specifically 8 Pa). No high-temperature heat treatment is used throughout the process; the internal porous structure is maintained without collapse by ice crystal support. The complete coaxial spinning process provided by this invention is continuous and stable, capable of producing complete filaments uninterruptedly for extended periods.

[0036] In this invention, multiple segmented water washing can gradually dissolve residual solvents and free acids inside the fiber, avoiding long-term retention of residual components that could damage the internal micro-pores; low-temperature freezing relies on ice crystal physical support to lock the porous skeleton formed during the molding stage, preventing pore shrinkage and collapse caused by high-temperature drying; vacuum low-temperature sublimation drying has no melting heat treatment throughout the process, preserving the continuous hierarchical porous structure built during the spinning stage to the greatest extent.

[0037] The present invention also provides a layered porous core-sheath structure aerogel fiber prepared by the above preparation method, wherein the fiber sheath of the layered porous core-sheath structure aerogel fiber is a dense porous PAN sheath, and the core layer is a continuous through-layered porous skeleton formed by DABA-TFP-COF self-assembly.

[0038] In this invention, the fiber sheath preferably has micron-sized fine pores with a pore size of 100-200 nm; the core layer preferably forms a large-scale continuous porous network with a pore size of 100-300 μm; the layered porous sheath-core structure aerogel fiber has a complete sheath-core boundary and no core liquid leakage or fiber breakage defects.

[0039] This invention also provides the application of the layered porous core-shell structure aerogel fiber described in the above technical solution in the field of low-temperature thermal insulation and lightweight thermal insulation functional materials.

[0040] In this invention, the temperature range of the low-temperature insulation is -20 to 0°C. In this invention, the temperature range of the lightweight thermal insulation material is 20 to 150°C.

[0041] In this invention, the tensile strength of the layered porous core-shell structure aerogel fiber is not less than 3 MPa, and more preferably 3.5 to 4.3 MPa.

[0042] The fine porous outer layer of the fiber prepared by this invention forms a physical protective layer, improving the fiber's tensile and compressive properties; the large-scale interconnected honeycomb porous network of the inner layer can bind the stationary medium, achieving excellent thermal insulation effect. It simultaneously solves the industry problem that the high porosity and mechanical properties of traditional aerogel fibers cannot be balanced, and can be applied to the preparation of various lightweight low-temperature thermal insulation materials.

[0043] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.

[0044] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0045] The present invention relates to embodiments and comparative examples, and adopts a unified testing method as follows: Fiber tensile tests were conducted using a universal testing machine with an effective fiber length of 5 cm, a tensile rate of 5 mm / min, and an ambient temperature of 25 ℃ and normal pressure. Each group of samples was tested in parallel for 5 times and the average value was taken. Field emission scanning electron microscopy was used to observe the intact cross-section of the fiber, the core-skin interface, and the porous morphology of the core layer.

[0046] Fiber samples of equal thickness were laid flat on a constant-temperature heating platform, and temperature changes were recorded in real time by infrared thermal imaging. Steady-state temperature differences were collected to compare the thermal insulation capabilities of each group of fibers.

[0047] In the following examples and comparative examples, the preparation method of DABA-TFP-COF is as follows: 0.286 mg of 2,5-diaminobenzenesulfonic acid (DABA, 99%) and 0.214 mg of 1,3,5-tricarboxymethylresorcinol (TFP, 97%) were weighed; DABA was dissolved in 10 mL of dimethyl sulfoxide (DMSO) and TFP was dissolved in 15 mL of dimethyl sulfoxide (DMSO). Both were placed in an ultrasonic machine and ultrasonicated until completely dissolved into a clear solution. Then, the DABA solution was poured into the TFP solution, shaken evenly, and placed in a 60°C oven for 5 days to obtain DABA-TFP-COF.

[0048] Example 1 Step 1: Preparation of PAN spinning solution: Weigh PAN powder and add it to dimethyl sulfoxide. Stir at room temperature for 12 hours to prepare a uniform and transparent PAN spinning solution of 250 mg / mL. Step 2: Preparation of COF dispersion in the core layer: DABA-TFP-COF powder is dissolved in dimethyl sulfoxide, ultrasonically vibrated for 2 hours, sealed and protected from light, and reacted at a constant temperature of 60℃ for 6 days. After cooling, it is allowed to stand for degassing for 8 hours to prepare a stable core layer dispersion of 20 mg / mL. Step 3: Coaxial wet spinning: Prepare a coagulation bath with a volume fraction of 0.03% p-toluenesulfonic acid aqueous solution, pH≈2.8; the sheath push flow rate is 100μL / min, the core push flow rate is 80μL / min, the two fluids are extruded simultaneously, and the fiber is completely immersed in the coagulation bath and soaked at room temperature for 30min to obtain nascent sheath-core hydrogel fiber. Step 4: Post-processing: The nascent core-sheath hydrogel fiber is immersed in deionized water for 20 minutes and washed 4 times. After washing, it is laid flat in a -20℃ freezer for 12 hours. It is then transferred to a freeze-drying chamber and dried under vacuum conditions of 8 Pa and -45℃ for 36 hours to obtain the finished multi-layered porous coaxial core-sheath aerogel fiber.

[0049] The microstructure of the prepared aerogel fibers is as follows: Figure 1 and Figure 2 As shown, the core and sheath are clearly demarcated, with the core layer forming a continuous, interconnected honeycomb porous network. The pore size distribution in the sheath is 100–200 nm, while that in the core layer is 100–300 μm. Tensile testing results show a fiber breaking strength of 3.5 MPa; in a 40°C constant-temperature platform thermal insulation test, the steady-state temperature difference of the fabric is 6.6°C.

[0050] Example 2 The preparation process in this embodiment is completely the same as in Example 1, except that the coagulation bath is changed to a methanesulfonic acid aqueous solution and the pH is adjusted to approximately 2.8. The other stock solution ratio, spinning pump speed, water washing and freeze drying parameters remain unchanged to obtain the corresponding fiber sample.

[0051] The microstructure of the prepared fibers is as follows Figure 2 As shown, the complete skin and core are clearly demarcated, and the core layer forms a continuous and interconnected honeycomb porous network; the tensile strength is 3.6 MPa, and the steady-state temperature difference on a 40℃ hot table is 6.2℃.

[0052] Example 3 The preparation process in this embodiment is completely the same as in Example 1, except that the coagulation bath is changed to an aqueous sulfuric acid solution and the pH is adjusted to approximately 2.8. The other stock solution ratio, spinning pump speed, water washing and freeze drying parameters remain unchanged, and the corresponding fiber sample is obtained.

[0053] The microstructure of the prepared fibers is as follows Figure 2 As shown, the core and skin are clearly separated, and the core layer forms a continuous and interconnected honeycomb porous network; the tensile strength is 4.3 MPa. The steady-state temperature difference under different temperature heating stages is shown in Table 1. Table 1. Steady-state temperature difference of heating stages at different temperatures

[0054] Comparative Example 1 The preparation of spinning solution, core solution, coaxial spinning pump speed, water washing, and freeze drying were all consistent with those in Example 1, except that the acidic coagulation bath was replaced with pure deionized water, and no acidic components were used.

[0055] After molding, the COF nanosheets in the core layer are highly aggregated, the layers are stacked larger, and the microstructure of the fiber is as follows: Figure 2 As shown, the fiber tensile strength is only 3.2 MPa, and the steady-state temperature difference on a 40℃ hot table is 5.1℃.

[0056] In summary, this invention employs a coaxial spinning process combining a PAN sheath with an acid-induced COF self-assembled core layer. By relying on an acidic coagulation bath to precisely control the multi-layered porous structure of the core layer, the dense sheath and the continuous honeycomb core layer work together to simultaneously achieve excellent mechanical properties and thermal insulation capabilities. The entire process is conducted at low temperatures, eliminating the need for high-temperature heat treatment. The spinning process is continuous and can be prepared in a coherent manner, effectively overcoming the shortcomings of existing aerogel fibers in balancing porosity and mechanical properties.

[0057] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hierarchical porous core-sheath structure aerogel fiber, characterized in that, Includes the following steps: Step 1: Dissolve polyacrylonitrile in an organic solvent to obtain polyacrylonitrile stock solution; Step 2: Disperse DABA-TFP-COF in an organic solvent to obtain a COF dispersion; Step 3: Using polyacrylonitrile stock solution as the sheath spinning solution and COF dispersion as the core spinning solution, coaxial wet spinning is carried out, and the fibers are extruded into an acidic aqueous solution coagulation bath to form nascent sheath-core hydrogel fibers. Step 4: The nascent core-skin hydrogel fibers are sequentially freeze-molded and vacuum freeze-dried to obtain the hierarchical porous core-skin structure aerogel fibers; There is no restriction on the order of steps 1 and 2.

2. The preparation method according to claim 1, characterized in that, In step 1, the organic solvent includes at least one of dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; The concentration of polyacrylonitrile in the polyacrylonitrile stock solution is 150~250 mg / mL.

3. The preparation method according to claim 1, characterized in that, In step 2, the organic solvent includes at least one of dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; The concentration of DABA-TFP-COF in the COF dispersion is 10~20 mg / mL; The dispersion includes: ultrasonic dispersion followed by a constant-temperature reaction; the ultrasonic dispersion time is 1-2 hours; the constant-temperature reaction temperature is 40-60°C, and the time is 6-8 days; After the isothermal reaction, the process further includes sequential cooling and static degassing; the cooling is natural cooling to room temperature; the static degassing time is 4~12h.

4. The preparation method according to claim 1, characterized in that, During the coaxial wet spinning process, the propulsion speed of the sheath spinning solution is 100~200μL / min, the propulsion speed of the core spinning solution is 80~180μL / min, and the propulsion speed of the sheath spinning solution is greater than that of the core spinning solution.

5. The preparation method according to claim 1, characterized in that, The acidic aqueous solution includes at least one of hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution, methanesulfonic acid aqueous solution, and p-toluenesulfonic acid aqueous solution; the pH value of the acidic aqueous solution coagulation bath is 2.5~2.8; The impregnation molding time is 20-30 minutes.

6. The preparation method according to claim 1, characterized in that, Before the cryogenic molding process, the nascent core-sheath hydrogel fiber is soaked and washed multiple times. The soaking and washing are carried out at room temperature using deionized water. The soaking and washing time is 10-30 minutes per soaking and washing, and the number of soaking and washing cycles is 3-5.

7. The preparation method according to claim 1, characterized in that, The freezing temperature is -18~-25℃, and the time is 6~12h; The vacuum freeze-drying temperature is -40~-50℃, the time is 24~48h, and the vacuum degree of the drying chamber is ≤10Pa.

8. The layered porous core-shell structure aerogel fiber prepared by the preparation method according to any one of claims 1 to 7, characterized in that, The fiber skin of the hierarchical porous core-skin structure aerogel fiber is a dense porous PAN skin, and the core layer is a continuous, interconnected hierarchical porous skeleton formed by DABA-TFP-COF self-assembly.

9. The layered porous core-sheath structure aerogel fiber according to claim 8, characterized in that, The pore size of the fiber sheath is 100~200nm; the pore size of the core layer is 100~300μm.

10. The application of the layered porous core-shell structure aerogel fiber as described in claim 8 or 9 in the field of low-temperature thermal insulation and lightweight thermal insulation functional materials.